2003
DOI: 10.1002/ptr.1330
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of in vitro antiviral activity in methanol extracts against influenza virus type A from Korean medicinal plants

Abstract: Methanol extracts from 101 Korean medicinal plants were tested for inhibitory activity against influenza virus type A by means of a modified haemagglutination inhibition (HI) test. MM-57, MM-72, MM-104 and MM-110, four of 101 extracts tested exhibited strong anti-influenza virus type A activity at concentration ranges of 0.78-6.25 mg/mL, 0.78-3.13 mg/mL, 0.78-1.56 mg/mL and 0.0975-0.39 mg/mL, respectively. The extracts MM-57, MM-72 and MM-110 showed very strong anti-influenza virus type A activity in the range… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…Similarly, the low IC 50 value of these plants confirms the potential of Cholistani plants against AIV. The similar results are reported by other researchers like (Park, 2003) have reported anti AIV activity from methanol extracts of four Korean medicinal plants. (Lee et al, 2016; et al, 2019) have reported anti AIV activity from n-hexane and ethyl acetate extracts of green tea.…”
Section: Discussionsupporting
confidence: 91%
“…Similarly, the low IC 50 value of these plants confirms the potential of Cholistani plants against AIV. The similar results are reported by other researchers like (Park, 2003) have reported anti AIV activity from methanol extracts of four Korean medicinal plants. (Lee et al, 2016; et al, 2019) have reported anti AIV activity from n-hexane and ethyl acetate extracts of green tea.…”
Section: Discussionsupporting
confidence: 91%
“…Plants have a long evolutionary history of developing resistance against viruses and have increasingly drawn attention as potential sources of antiviral drugs. For instance, many plant extracts and compounds of plant origin have been shown to have activity against influenza viruses (Park, 2003;Koehn and Carter, 2005). At present, plant and herb resources are unlimited, have provided mankind with remedies for many infectious diseases and continue to play a major role in primary health care as therapeutic remedies in developing countries.…”
Section: Discussionmentioning
confidence: 99%
“…24 Influenza viruses are classified into type A, B and C, with type A appearing to be the most notorious candidate. 25 The epidemiology of influenza virus type A and B is distinctive due to their seasonality and antigenic variation. The gradual antigenic drift of influenza virus type A and B coupled with occasional antigenic shift make it difficult to control the infection.…”
Section: Inhibition Of H1n1 Influenza Virusmentioning
confidence: 99%